Ru(II) phenanthroline complex as catalyst for chemoselective hydrogenation of nitro-aryls in a green process - Deshmukh, Amit A.; Prashar, Atul K.; Kinage, Anil K.; Kumar, Rajiv; Meijboom, Reinout (Industrial & Engineering Chemistry Research, 2010)
Ru(II) Phenanthroline [Ru(II)(Phen)(n) where n = 1,2,3] complexes were used as highly chemoselective catalysts for hydrogenation of nitro aryls using molecular hydrogen in an aqueous media. Water, universal solvent, was used as a reaction mixture for hydrogenation of nitro-aryls to make the process green. The chemoselectivity in hydrogenation of substituted nitrobenzene to substituted aniline was obtained as high as >99% at about complete conversion of substituted nitrobenzene. The parametric effects, including effect of solvent, effect of ligand, effect of metal to ligand ratio, effect of temperature and pressure, were studied in detail to obtain the best results. The Ru(Phen)(n) was characterized by FTIR, UV-vis, and XPS.

Reaction kinetics for catalytic hydrogenation of quinoline to decahydroquinoline as liquid organic hydrogen carrier - Bagwan, Farahanaz M.; Kinage, Anil K.; Vasireddy, Satyam Naidu (International Journal of Hydrogen Energy, 2024)
The catalytic hydrogenation of quinoline to decahydroquinoline (DHQ) formation is studied for various parameters such as temperature, hydrogen pressure, reaction time, solvents, reactant-to-solvent ratio, and catalyst loading over 5%Pd loaded on alumina (Pd/Al2O3) to obtain optimal reaction conditions. The hydrogen uptake of quinoline in the liquid phase reaction using isopropylalcohol (IPA) is studied in an autoclave reactor. The optimum reaction parameters of 50 bar H2 pressure and 175oC with reactant to solvent ratio of 1:9 for reaction time of 5 h are observed. The effect of IPA solvent showed that hydrogen uptake of 6.91 wt% with complete hydrogenation of quinoline and DHQ yield of more than 99% is observed. The reaction kinetic model is developed for a simplified reaction mechanism and is simulated using the Markov Chain Monte Carlo (MCMC) simulation tool to predict the rate constants and the experimental observations are validated with the model predictions. The activation energy for quinoline hydrogenation to py-THQ formation is estimated to be 136.57 kJ/mol. It is envisaged that quinoline hydrogenation to pz-THQ is the rate-limiting step in the DHQ formation.
Keywords: Decahydroquinoline (DHQ); Hydrogen uptake; Liquid organic hydrogen carrier (LOHC); Markov chain Monte Carlo (MCMC) simulation; Thermal screening unit (TSU); tool

Rongalite-promoted self-dimerization of 3-acylidene-2-oxindoles: a diastereoselective route to synthesis of bispirooxindoles - Chaudhari, Suryakant S.; Nichinde, Chandrakant B.; Patil, Baliram R.; Girase, Amardipsing S.; Kaulage, Sandeep H.; Kinage, Anil K. (Organic & Biomolecular Chemistry, 2025)
A facile and efficient one-pot rongalite-mediated self-dimerization of 3-acylidene-2-oxindoles has been developed for the diastereoselective synthesis of highly functionalized dispirocyclopentanebisoxindoles. The reaction proceeds via a domino sequence involving intermolecular Michael addition followed by intramolecular aldol cyclization under basic conditions. Rongalite, an inexpensive and readily available reagent (similar to\$0.03 per g), plays a crucial role in promoting the transformation, offering significant advantages such as operational simplicity, step economy, scalability to gram-scale synthesis, and potential for post-functionalization. This methodology provides an efficient route to structurally complex oxindole frameworks with high stereocontrol, demonstrating broad synthetic utility.

Reaction kinetics for dehydrogenation of decahydroquinoline to quinoline for hydrogen generation - Bagwan, Farahanaz M.; Dadkar, Sarthak S.; Kinage, Anil K.; Vasireddy, Satyam Naidu (Chemical Engineering & Technology, 2026)
Catalytic dehydrogenation of decahydroquinoline (DHQ) to quinoline is a promising pathway for hydrogen release in liquid organic hydrogen carrier systems. In this work, solvent-free DHQ dehydrogenation over Pd/Al2O3 is systematically investigated to evaluate hydrogen release performance and reaction kinetics. High DHQ conversion (83.9%) and degree of dehydrogenation (82.7%) are achieved at optimal reaction conditions. A power-law kinetic model based on a simplified reaction mechanism is developed and simulated using a Markov Chain Monte Carlo (MCMC) approach for estimation of rate constants and validation of concentration profiles with experimental data. The apparent activation energies are determined to be 45.85 kJ/mol for DHQ to 5,6,7,8-tetrahydroquinoline (bz-THQ) and 185.43 kJ/mol for bz-THQ to quinoline formation, identifying latter as the rate-limiting step. This framework provides mechanistic insight and supports the potential of DHQ as an efficient hydrogen carrier.
Keywords: Decahydroquinoline (DHQ); degree of dehydrogenation; Dehydrogenation; rate-limiting step; Reaction kinetics; Weisz-Prater criterion